Study of diazepam effects on Ehrlich ascites carcinoma and anxiety responses in male SHK mice - T. S. Kalinina; A. A. Shimshirt; K. V. Lisitskaya; A. V. Volkova; N. V. Kudryashov (LLC "Publisher OKI", 2022)
Сomorbidity of malignant tumors and affective disorders is an urgent problem. It is known that some psychotropic drugs may adversely influence the growth of malignant tumors and metastasis; in the experiment, a connection between neurotransmitters and tumors was established. Earlier, in experiments on mice, the ability of diazepam to stimulate the growth of Ehrlich's ascites carcinoma was demonstrated.   The aim of this study was to assess the role of central and peripheral benzodiazepine receptor sites in the stimulating effect of diazepam on Ehrlich's carcinoma. The effects of diazepam (0.03 and 3.0 mg / kg, intragastric) on the development of Ehrlich's ascites carcinoma and an orientation-exploratory response in the "open field" test on male SHK mice were studied. It was found that diazepam at a dose of 0.03 mg / kg, but not at a dose of 3 mg / kg, increases the cellularity of the malignant ascites. At the same time, diazepam in both doses studied causes an increase in the peripheral motor activity of mice, which indicates an increase in anxiety reactions. It was found that flumazenil, but not PK11195, attenuates the stimulating effect of diazepam on Ehrlich's ascites carcinoma and inhibits the pro-anxiogenic effect of a small dose of diazepam. The results obtained allow us to conclude that there is no associative relationship between the pro-tumor effect of diazepam and its effect on anxiety responses, but at the same time, the participation of central mechanisms in the stimulating effect of benzodiazepine on the tumor cannot be ruled out.